1955
DOI: 10.1104/pp.30.4.297
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soil-Moisture Content on the Rate of Photosynthesis and Respiration in Ladino Clover (Trifolium Repens L.).

Abstract: Numerous studies have been conducted to evaluate the effect of variations in soil-moisture on plant behavior. The objective of many of these investigations has been to determine the most suitable irrigation practices for obtaining good yields and quality in crop plants. Relatively moisture content on the net CO2 exchange of apple leaves over a 4-week period. Plants were allowed to extract 20, 40, 60, 80 and 100 % of the available soil moisture and were then watered to field capacity.They write, " Apple trees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
1

Year Published

1964
1964
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 4 publications
0
11
1
Order By: Relevance
“…Nevertheless, this observation agrees with some published studies in other species (Lawlor, 1976;Loboda, 1993;Flexas et al, 2005). However, several other authors have found different results on the effect of water stress on respiration, ranging from decrease (Brix, 1962;Brown and Thomas, 1980;Palta and Nobel, 1989;Escalona et al, 1999;Ghashghaie et al, 2001;Haupt-Herting et al, 2001) to stimulation (Upchurch et al, 1955;Shearmann et al, 1972;Zagdań ska, 1995). In all cases, as in this study, changes in respiration were much less than those in photosynthesis, causing a significant increase in the respiration/photosynthesis ratio under water stress, indicating that the role of respiration becomes more important as water stress develops.…”
Section: The Effect Of Water Stress On Leaf Respirationcontrasting
confidence: 53%
“…Nevertheless, this observation agrees with some published studies in other species (Lawlor, 1976;Loboda, 1993;Flexas et al, 2005). However, several other authors have found different results on the effect of water stress on respiration, ranging from decrease (Brix, 1962;Brown and Thomas, 1980;Palta and Nobel, 1989;Escalona et al, 1999;Ghashghaie et al, 2001;Haupt-Herting et al, 2001) to stimulation (Upchurch et al, 1955;Shearmann et al, 1972;Zagdań ska, 1995). In all cases, as in this study, changes in respiration were much less than those in photosynthesis, causing a significant increase in the respiration/photosynthesis ratio under water stress, indicating that the role of respiration becomes more important as water stress develops.…”
Section: The Effect Of Water Stress On Leaf Respirationcontrasting
confidence: 53%
“…There is evidence that following a period of desiccation, rates of photosynthesis under high light (2,11,21,25) present before desiccation. For example, increased root resistance could result in low leaf water potentials, and incomplete stomatal opening might then be attributable to low water potentials rather than to an after-effect of desiccation acting on the stomatal mechanism itself.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that following a period of desiccation, rates of photosynthesis under high light (2,11,21,25) and transpiration (11,17,21) may remain lower, resistance to water movement through the root system may be larger (17,18), and stomata may open less in light than do those of nondesiccated control plants (12 Leaf water potential was measured by the isopiestic technique with thermocouple pyschrometers which could accommodate either intact leaves (6) or excised leaf tissue (4,10). Several hours before measurements were made, the experimental tissue was rinsed in distilled water and permitted to dry in order to remove surface contaminants.…”
mentioning
confidence: 99%
“…Several metabolic processes, which are completely dependent upon phosphorylated intermediates, are noticeably affected by moisture stress conditions. Photosynthetic rate decreases markedly in severely stressed plants (13). Rate of fixation of CO2 in the dark decreases (12).…”
mentioning
confidence: 99%